Assessing Recovery: Examination of Greenhouse Gas Fluxes, Soil Characteristics, and Vegetation in Sediment Enhanced Marshes - Danielle C. Perry; Nia Bartolucci; Cathleen Wigand; Kenneth B. Raposa; Joseph Loffredo; Wenley Ferguson; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Towards a global barcode reference library for subterranean fauna - Michelle T. Guzik; Jake Thornhill; Mieke van der Heyde; Danielle N. Stringer; Nicole E. White; Mattia Saccò; Perry G. Beasley-Hall; Paul Nevill; Rachael A. King; Steven J.B. Cooper; Andrew D. Austin (Science of The Total Environment, 2026)

Is our understanding of aquatic ecosystems sufficient to quantify ecologically driven climate feedbacks? - Corday R. Selden; Richard LaBrie; Laura C. Ganley; Daniel R. Crocker; Ohad Peleg; Danielle C. Perry; Hannah G. Reich; Matthew Sasaki; Patricia S. Thibodeau; Jana Isanta‐Navarro (Global Change Biology, 2024)
The Earth functions as an integrated system—its current habitability to complex life is an emergent property dependent on interactions among biological, chemical, and physical components. As global warming affects ecosystem structure and function, so too will the biosphere affect climate by altering atmospheric gas composition and planetary albedo. Constraining these ecosystem‐climate feedbacks is essential to accurately predict future change and develop mitigation strategies; however, the interplay among ecosystem processes complicates the assessment of their impact. Here, we explore the state‐of‐knowledge on how ecological and biological processes (e.g., competition, trophic interactions, metabolism, and adaptation) affect the directionality and magnitude of feedbacks between ecosystems and climate, using illustrative examples from the aquatic sphere. We argue that, despite ample evidence for the likely significance of many, our present understanding of the combinatorial effects of ecosystem dynamics precludes the robust quantification of most ecologically driven climate feedbacks. Constraining these effects must be prioritized within the ecological sciences for only by studying the biosphere as both subject and arbiter of global climate can we develop a sufficiently holistic view of the Earth system to accurately predict Earth's future and unravel its past.

Association of ambient extreme heat with pediatric morbidity: a scoping review - Danielle Uibel; Rachit Sharma; Danielle Piontkowski; Perry E. Sheffield; Jane E. Clougherty (International Journal of Biometeorology, 2022)

A resource-poor developmental diet reduces adult aggression in male Drosophila melanogaster - Danielle Edmunds; Stuart Wigby; Jennifer C. Perry (Behavioral Ecology and Sociobiology, 2021)
Aggressive behaviours occur throughout the animal kingdom and agonistic contests often govern access to resources. Nutrition experienced during development has the potential to influence aggressive behaviours in adults through effects on growth, energy budgets and an individual’s internal state. In particular, resource-poor developmental nutrition might decrease adult aggression by limiting growth and energy budgets, or alternatively might increase adult aggression by enhancing motivation to compete for resources. However, the direction of this relationship—and effects of developmental nutrition experienced by rivals—remains unknown in most species, limiting understanding of how early-life environments contribute to variation in aggression. We investigated these alternative hypotheses by assessing male-male aggression in adult fruit flies, Drosophila melanogaster , that developed on a low-, medium- or high-resource diet, manipulated via yeast content. We found that a low-resource developmental diet reduced the probability of aggressive lunges in adults, as well as threat displays against rivals that developed on a low-resource diet. These effects appeared to be independent of diet-related differences in body mass. Males performed relatively more aggression on a central food patch when facing rivals of a low-resource diet, suggesting that developmental diet affects aggressive interactions through social effects in addition to individual effects. Our finding that resource-poor developmental diets reduce male-male aggression in D. melanogaster is consistent with the idea that resource budgets mediate aggression and in a mass-independent manner. Our study improves understanding of the links between nutrition and aggression. Significance statement Early-life nutrition can influence social behaviours in adults. Aggression is a widespread social behaviour with important consequences for fitness. Using the fruit fly, Drosophila melanogaster , we show that a poor developmental diet reduces aspects of adult aggressive behaviour in males. Furthermore, males perform more aggression near food patches when facing rivals of poor nutrition. This suggests that early-life nutrition affects aggressive interactions through social effects in addition to individual effects.

Population ecology of the snail Melampus bidentatus in changing salt marsh landscapes - Roman Zajac; Erin Kelly; Danielle Perry; Ivana Espinosa (Marine Ecology, 2017)
We studied the population ecology of the snail Melampus bidentatus in relation to patch composition and landscape structure across several salt marsh systems in Connecticut, USA . These marshes have changed significantly over the past 40–50 years including loss of total area, increased areas of short Spartina alterniflora , and decreased areas and fragmentation of Spartina patens . These changes are consistent with tidal inundation patterns that indicate frequent flooding of high marsh areas. Melampus bidentatus densities were highly variable, both among different salt marsh systems and locations within specific marshes, but were generally similar among short Sp. alterniflora and Sp. patens patches within locations. Densities were lowest where the marsh was regularly inundated at high tide and only remnant Sp. patens patches remained. Almost no snails were found in bare patches. Areas that had large Sp. patens patches adjacent to short Sp. alterniflora supported the highest M. bidentatus densities. Population size‐structure varied significantly among patch types, with higher proportions of large individuals in short Sp. alterniflora and hummocked Sp. patens patches than in large and remnant Sp. patens patches. This was likely due to size‐selective predation and/or higher snail growth rates due to better food resource conditions in short Sp. alterniflora patches. Egg mass densities and the number of eggs per egg mass were highest in short Sp. alterniflora . Our results indicate that M. bidentatus is resilient to the level and patterns of salt marsh change evident at our study sites. Indeed, snail densities were significantly higher than reported in other field studies, suggesting that increased patch areas of short Sp. alterniflora and associated environmental conditions at our study sites may provide more favorable habitats than previously when marshes were dominated by extensive Sp. patens meadows. However, there may be threshold conditions that could overwhelm the ability of M. bidentatus to maintain itself within salt marsh systems where changes in hydrology, sedimentation and other factors lead to increased numbers of bare patches and ponds and loss of short Sp. alterniflora and Sp. patens . Studies of the responses of resident and transient fauna to salt marsh change are critically needed in order to better understand the implications for salt marsh ecosystem dynamics and services.

Chromosome size and origin as determinants of the level of CENP-A incorporation into human centromeres - Danielle V. Irvine; David J. Amor; Jo Perry; Nicolas Sirvent; Florence Pedeutour; K. H. Andy Choo; Richard Saffery (Chromosome Research, 2004)